2020
DOI: 10.7821/naer.2020.1.534
|View full text |Cite
|
Sign up to set email alerts
|

Reflection on the Dangers of ‘cultural racism’ in Intercultural Education

Abstract: This paper assesses the dangers of the use of the concept ‘culture’ in present political and educational rhetoric. The first section offers a critique of the use of the term ‘culture’ in the so-called intercultural educational efforts. It asserts that ‘culture’ in its present use is a proxy for ‘race’ and supports views, which ignore diversity and suggest, purposely or not, an homogeneity which can easily spread into the sphere of biological resemblances and differences. The paper, then, identifies possible al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
0
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
0
0
1
Order By: Relevance
“…As with other research, we have confirmed that there is a tendency amongst immigrant students to form groups by nationality, in other words, to create "ghettos" [1,18,20,53]. This usually occurs at playtime and when they do not speak the host language well.…”
Section: Discussionsupporting
confidence: 88%
“…As with other research, we have confirmed that there is a tendency amongst immigrant students to form groups by nationality, in other words, to create "ghettos" [1,18,20,53]. This usually occurs at playtime and when they do not speak the host language well.…”
Section: Discussionsupporting
confidence: 88%
“…Las entidades que han colaborado con las investigaciones son todas las entidades sociales que intervienen con menores en el barrio de Entrevías. Estas asociaciones tienen características similares de intervención socioeducativa y practican metodologías demostradas en otras investigaciones, como puede ser la educación para la paz desde el deporte (Lamoneda et al, 2017), trabajar las habilidades sociales desde la lectura (Gutiérrez Fresneda, 2016), derecho a jugar (Payà Rico y Bantul, 2021), educación intercultural (Bekerman, 2020), el entorno como herramienta educativa (García y Carrascal, 2014) y educar desde el apego (Pitilas et al, 2016). En esta investigación se quiere conocer si las metodologías usadas en estos centros favorecen un mayor aprendizaje de la educación para el desarrollo sostenible.…”
Section: Método De Investigaciónunclassified
“…La integración de la tecnología digital en el día a día, y su repercusión en la sociedad actual, es un hecho irrefutable (Román et al, 2016;Sánchez-López, Pérez-Rodríguez & Fandos-Igado, 2019), no solo a nivel general, sino también en contextos inclusivos (Arnaiz, de Haro-Rodríguez & Maldonado, 2019;Bonilladel-Rio, García-Ruíz y Pérez, 2018) e interculturales (Bekerman, 2020;Eliyahu-Levi & Ganz-Meishar, 2020). Innovar no es una moda educativa (Cabero-Almenara & Roig-Vila, 2019;Rodríguez de las Heras, 2015), sino una forma de mejorar y transformar los procesos de enseñanza-aprendizaje con nuevos medios, entre los cuales cabe destacar los que conforman la tecnología educativa (Prendes, 2018).…”
Section: Introductionunclassified